Preparation of Au-BiVO4 heterogeneous nanostructures as highly efficient visible-light photocatalysts - Cao, Shao-Wen (2012)
Au-BiVO4 heterogeneous nanostructures have been successfully prepared through in situ growth of gold nanoparticles on BiVO4 microtubes and nanosheets via a cysteine-linking strategy. The experimental results reveal that these Au-BiVO4 heterogeneous nanostructures exhibit much higher visible-light photocatalytic activities than the individual BiVO4 microtubes and nanosheets for both dye degradation and water oxidation. The enhanced photocatalytic efficiencies are attributed to the charge transfer from BiVO4 to the attached gold nanoparticles as well as their surface plasmon resonance (SPR) absorption. These new heteronanostructures are expected to show considerable potential applications in solar-driven wastewater treatment and water splitting.